Kształtowanie konkurencyjności regionalnej (przykład województwa pomorskiego) - Paczoski, Andrzej; Kempa, Jarosław (Creation of the Regional Competition (Pomeranian Voivodeship example), 2008)
The article covers the problem of regional competition (definition and factors of regional competition) and attemption of the evaluation „ The Pomeranian Voivodeship Development Strategy". There were presented: complicated meaning of the regional competition concept and detailed factors which determined the position of regional competition. Analysis of voivodeship competition was based on the A.Godet's conception which distinguish several forms of voivodeship strategies. In this context there were accomplished comparison between weak sides and exterior chances of Pomeranian Voivodeship. Then there were defined main development dilemmas. Simultaneously it was made the analysis the allocation of the finance on the individual targets of the Regional Operating Programme for the Pomeranian Voivodeship (in the 2007-2013 period), which is the second after the Regional Development Integrated Operating Programme in the 2004-2006 period measure for realization The Pomeranian Voivodeship Development Strategy by local government. After the analysis, the recognition has been done: Pomeranian Local Government will intend to realize the competitive strategy based on the strong support the enterprises and create the information society.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 140-154